FAKTOR-FAKTOR YANG MEMENGARUHI GETOK TULAR PADA USAHA RESTORAN WARALABA DI JAKARTA - Rembulan, Glisina Dwinoor (Jurnal Pengabdian dan Kewirausahaan, 2018)
In 2017 the number of franchise turnover in Indonesia reached 200 trillion rupiah with a composition of 65% contributed by foreign franchises and 35% came from local franchises. The food and beverage industry sector also contributes 80 percent of the total franchise turnover in Indonesia. Based on data from the Ministry of Tourism of Indonesia, restaurant businesses with medium and large scale increased in number even though based on the percentage of growth slowed down. From 2008-2011 the restaurant business experienced an increase of 600 units of restaurants. This explains that restaurant businesses, especially food and beverages, have a high appeal to people's consumption choices. Various factors of attraction and weakness of a franchise restaurant is not uncommon to be a discussion and recommendation of the community either directly or online media. This study aims to measure whether influenza is influenced by the quality of food, the quality of restaurant officers, and the appearance of the restaurant. This study used multiple regression and SPSS 24 to analyze the data. The result of this research explains that partially word of mouth is not influenced by the quality of food, the quality of the restaurant officer, and the appearance of the restaurant. Simultaneously, these factors have an effect on the word of mouth. The use and socialization of the voting system and comments on the factors in this study can help the restaurant franchise business in the formation and dissemination of public spirits. Keywords: Restaurant, franchise, word of mouth